The effect of visual and auditory elements on patrons' liquor-ordering behavior: An empirical study. (May 2016) - Lee, Dongmin; Moon, Junghoon; Rhee, Cheul; Cho, Dongwoo; Cho, Jongpyo
Abstract: This study aims to empirically investigate the effect of music and visual congruency with a type of liquor in a bar. Specifically, it examines the effect of atmospheric elements' congruency with wine on patrons' liquor-ordering behavior and their expenditures. As most Koreans associate wine with French culture, French auditory and visual cues were used to investigate the effect of congruency. A total of 650 receipts from two different branches of a bar were collected for four weeks. The study found that in the visual congruence condition, the ratio of wine expenditure to the total expenditure of a table and the ratio of liquor expenditure to the total expenditure of a table increased. When the auditory congruence condition was implemented, the probability of ordering wine increased. There was no interaction effect. Implications based on the findings are discussed in the final section of the study.